Complex Evaluation of Light Sources in Case of Electric Power Cost Increase - Y. N. Kolesnik; A. V. Ivaneychik (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper gives complex evaluation of efficiency of incandescent lamps, luminescent and light-emitting-diode (LED) light sources in case of electric power price increase. On the basis of experimental table lamp electric power indices of light-emitting-diode (LED) light sources with equivalent luminous flux have been determined. Dependences of main indices of economic efficiency of various light sources on their operational regimes have been obtained and rate of influence on these indices of electric power price increase have been determined. Economically justified variants and conditions for application of various light sources have been substantiated.